Markers of subclinical atherosclerotic disease in HIV-infected individuals - Pulin K. Gupta; Manu Gupta; Ashok K. Lal; Anil Taneja; Rajesh S. Taneja; Bharat B. Rewari (Elsevier, 2018)
Background: Wider access to antiretroviral treatment (ART) has resulted in a decline in the number of people dying due to AIDS-related causes. However, with this increased longevity, accelerated rates of cardiovascular and atherosclerotic diseases are on the rise. We hypothesised that the prevalence of atherosclerotic cardiovascular diseases is greater in HIV/AIDS patients as compared to the normal population. Thus, we aimed to study the predictors of subclinical atherosclerotic disease in HIV-infected individuals. Methods: In total, 168 HIV-positive individuals below 45 years of age (124 [73.08%] on ART and 44 [26.2%] ART naive) along with 150 age- and sex-matched healthy controls were recruited for this cross-sectional observational study. Carotid intimal medial thickness (cIMT), a surrogate marker of atherosclerosis, was assessed by a carotid colour doppler ultrasound and a mean of four measurements (both sides) were taken. cIMT was correlated with the age of the individuals, duration and type of ART, duration of disease and the level of immunodeficiency (CD4 cell count) along with conventional cardiac risk markers. Results: In 168 HIV-positive individuals, the mean CD4 cell count was 332.41 ±17.1 cells/mm3. The mean cIMT of all HIV-positive individuals was 0.712 ±0.039 mm (0.596-0.840 mm) as compared to 0.616 ±0.023 mm (0.540-0.655 mm) in HIV-negative individuals (P>0.001). cIMT in HIV-positive individuals on ART (subgroup A) was 0.723 ±0.034 mm as compared to 0.682 ±0.038 mm in HIV-positive individuals not on ART (subgroup B) (P>0.01). Low CD4 cell counts, longer duration of HIV infection, exposure to ART and longer duration of ART were found to be independent predictors of a higher cIMT in HIV-positive subjects whereas age, diastolic blood pressure, low HDL, smoking and high BMI were predictors of high cIMT in HIV-negative controls. No difference was observed in cIMT among patients on different ART regimens but individuals who were on nevirapine had higher cIMT as compared to those who were on efavirenz, both non-nucleoside reverse transcriptase inhibitors (NNRTIs). Conclusions: Individuals with HIV infection (whether on ART or ART naive) have higher cIMT, and therefore a higher atherosclerotic burden, as compared to HIV-negative individuals. HIV infection itself, along with ART, overshadows conventional cardiac risk markers as a predictor of atherosclerotic disease in these individuals.